Oral hygiene interventions for people with disabilities: A Scoping Review, a Cochrane Review and a Realist Review - WALDRON, CATHERINE GERALDINE (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2019)
Abstract Title: Oral hygiene interventions for people with disabilities: A Scoping Review, a Cochrane Review and a Realist Review Author: Catherine Geraldine Waldron Background: Worldwide, the oral health of people with disabilities is poorer than that of the general population. The effectiveness of oral health interventions specifically designed for people with disabilities has not been systematically examined. The aim of this thesis was to identify what types of disabilities have been targeted, what types of interventions have been undertaken, what outcomes have been assessed and what are the contexts and mechanisms that facilitate or create barriers in relation to the success, or otherwise, of these interventions. Methods: The outcome from these reviews was realised through sequential application of multiple methods of data synthesis. Firstly, Scoping Review methodology was applied to systematically search for evidence in relation to what types of oral health interventions have been evaluated for people with disabilities. Secondly, a more focused Cochrane Review methodology explored the effectiveness of oral hygiene interventions for people with intellectual disabilities (ID). Thirdly, parallel to the Cochrane Review, Realist Review methodology was used to refine the theories in relation to how carer-led oral hygiene interventions are supposed to work. Results: The Scoping Review revealed a focus on therapeutic interventions for populations with disabilities (46%). Skill-based interventions (28%) were the next largest group of interventions, most of which were focused on oral hygiene skills or methods to teach these skills (90%), and most for a population with ID (48%). The Cochrane Review showed: (a) some benefits when a carer of a person with ID used a special manual toothbrush; (b) inconsistent findings between outcomes when an electric toothbrush was used by or for people with ID; (c) carers? oral health knowledge consistently improved following training. However, this training did not always impact on the carers? attitude or behaviour and resulted in only small reductions in the levels of gingival inflammation of the people with ID for whom they cared; (d) the benefit to the people with ID was shown to be greater when some level of monitoring of the carer?s behaviour was undertaken and (e) people with ID can acquire the skills to undertake some or all of the steps involved in toothbrushing. The Realist Review identified that the needs of the carers of people with ID, the type of oral care training provided and level of support provided to them, may all play an important role in the success of any carer-led oral hygiene intervention. The role of stakeholders in the planning and design of interventions and resourcing to ensure sustainability, were also identified as key elements supporting a successful outcome. Conclusion: The findings of the three reviews collectively provide a comprehensive insight, which did not exist previously, into oral hygiene interventions for people with ID: the types of interventions and populations targeted; the clinical and behavioural outcomes; and some contexts and mechanisms that have emerged as crucial to ensure success in future interventions. Each review has provided information that would not have been discovered by the others in isolation. Reviewing evidence, using parallel approaches, has provided depth to the findings reported in this thesis. All of the review approaches have their strengths and limitations: using the findings from them in combination has resulted in a whole that is greater than the sum of their parts. This thesis provides evidence to guide both practical and theoretical approaches for future oral hygiene interventions for people with intellectual disabilities.
APPROVED
Keywords: Disability; Oral health; Systematic Review